Patterns of Presentation, Morphology, and Referral in Pediatric Cataract: A Tertiary Center Study in a High-Consanguinity Population (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
BackgroundCataracts in children are a disease of outstanding etiology in terms of childhood blindness among all etiologic factors globally, and a disproportionately high burden in low-resource environments. Diagnostic and treatment lag times, caused by a paucity of screening facilities, a deficiency of collective awareness, and permeated by socioeconomic imperatives, make the visual morbidity of this disorder in Iraq largely disproportionate.Aim of the studyThe key purpose of the study was to assess and define the nature of clinical presentation of cataracts among children who presented in the Pediatric Ophthalmic Units of two leading tertiary care facilities in Baghdad.Patients and methodsThe cross-sectional observational study was conducted in Ibn Al Haitham Teaching Eye Hospital and Ghazi Surgical Specialties between September 2024 and April 2025. The sample included pediatric patients aged 1day to 12 years who had a positive diagnosis of cataract. The data on factors such as age at presentation, laterality, morphological subtype, family history, consanguinity, systemic and ocular association, and antecedent TORCH infections were accumulated using structured questionnaires and thorough clinical examination.ResultsThe analysis consisted of 84 pediatric patients (138 eyes) with cataract. Early presentation was predominant, with 28.6%⯠ of the cases presenting before or at 6 months of age, and a minor male dominance (52.4%). The commonest type of cataract was nuclear morphology (26.8portein), mixed (18.1portein), and total cataracts (18.1portein). The most common symptom reported was leukocoria (42.9⠄%), especially in males (p= 0.023), and a decline in visual acuity was more often reported in females (p= 0.015). The history of trauma rose considerably with age (p 0.001), and the use of systemic medications, in particular, steroids, was the highest in children aged 7 years to 9 years.ConclusionThe paediatric cataract features were dependent on age and gender, where Leukocoria was found to be more common among the younger male population, whereas poor visual acuity was higher among the older female population. High consanguinity and familial predisposition rates indicate a significant genetic factor, and delays in the diagnosis of older children indicate significant gaps in standard pediatric eye screening processes.